Clinical succes of alveolar bone distractions for implant rehabilitation: Review article - (:unkn) unknown (Nova Science Publishers, Inc., 2010)
Vertically deficient alveolar ridges represent a challenge for appropriate prosthetic rehabilitation. Nowadays osteointegrated implant use is the most popular treatment modality in such cases. A variety of techniques have been used to establish a suficant osseous tissue for supporting dental implants Onlay grafting and guided bone regeneration, are the frequently used surgical procedures. Distraction osteogenesis is an alternative augmentation technique providing the sufficient enlargement of the bone and soft tissue volume for the placement of dental implants. The purpose of this chapter was is to define the techniques and compare the complications and implant survival rates in localized alveolar deficiencies reconstructed by alveolar distraction osteogenesis. © 2010 Nova Science Publishers, Inc.